2022
DOI: 10.1007/s10495-021-01702-z
|View full text |Cite
|
Sign up to set email alerts
|

Benzofuran pyran hybrid prevents glucocorticoid induced osteoporosis in mice via modulation of canonical Wnt/β-catenin signaling

Abstract: Glucocorticoid induced osteoporosis (GIOP) is the second most leading cause of osteoporosis. We have identified a compound, a benzofuran pyran hybrid compound 4e that has osteogenic potential and we wanted to assess its efficacy in GIOP in male mice. We assessed the effect of dexamethasone and compound 4e on primary osteoblasts using various cell based and immunofluorescence assays. For in vivo studies we administered methylprednisolone and compound 4e as a prophylactic measure in male Balb/c mice for 28 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…Accordingly, our results revealed that DEX downregulated Wnt and osteocalcin mRNA expression, along with the protein expression of p-Akt in femur bone tissues. The obtained results are in line with earlier studies [15,21,[51][52][53]. Furthermore, we are first to demonstrate that these effects were greatly reversed by combining DEX with diosmin.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, our results revealed that DEX downregulated Wnt and osteocalcin mRNA expression, along with the protein expression of p-Akt in femur bone tissues. The obtained results are in line with earlier studies [15,21,[51][52][53]. Furthermore, we are first to demonstrate that these effects were greatly reversed by combining DEX with diosmin.…”
Section: Discussionsupporting
confidence: 92%
“…Osteoporosis will decrease the BV/TV, trabecular number, trabecular thickness, and increase trabecular spacing. In addition, analysis of cortical bone is an important indicator of pure anabolic effect in the process of osteoporosis (Song et al, 2020 ; Tripathi et al, 2022 ). Therefore, we tested these indicators in the GIOP mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…The adipogenic differentiation of bone marrow mesenchymal stem cells is facilitated by an increased expression of peroxisome proliferator-activated receptor gamma (PPAR-γ), thus leading to fat accumulation in the bone marrow and to bone loss in patients chronically supplemented with glucocorticoids. It is noteworthy that Wnt/β-catenin signaling pathway-activating compounds can prevent the development of GIOP [9], including vitamin D 3 (VD 3 ).…”
mentioning
confidence: 99%